Antimicrobial Susceptibility and b-Lactamase Production in Strains of Neisseria gonorrhoeae Isolated in Patients from the University Hospital "Dr. Manuel Núñez Tovar", Monagas State-Venezuela - J Lanz; H De Freitas; J Betancourt; N Núñez; W Velásquez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2004)
In order to determine the patterns of antimicrobial susceptibility and beta-lactamase production, 60 patients with sexually transmitted diseases were studied from the University Hospital "Dr. Manuel Nuñez Tovar" jurisdiction in Monagas State. Thirty-five N. gonorrhoeae strains (58,30%) were isolated, and they were grouped according to antimicrobial susceptibility and beta-lactamase production. A high resistance rate to penicillin (94.24%) and to tetracycline (97.14%) was detected. Out of the 33 N. gonorrhoeae strains resistant to penicillin, 15 (45.45%) did not produce beta-lactamase. On the other hand, in vitro sensitivity of N. gonorrhoeae to cefepime, cefoxitin and ceftriaxone was 97.14%, 94.29%, and 80.50%, respectively . In relation to the susceptibility to ofloxacin, it was found that 97,14% of the strains of N. gonorrhoeae showed sensitivity a this antimicrobial. treatment.